A Review of Enforcement of Military Discipline Law to Establish Professionalism of the National Army to Strengthen National Security and Resilience - Sungkono, Sungkono; Setyo, Amin; Suryokumoro, Herman; Kusumaningrum, Adi (Universitas Trunojoyo Madura, 2024)
AbstractLaw enforcement practices in the military environment are still not in line with sectoral egos. Law enforcement has not been able to guarantee substantive order, truth and justice. When carrying out law enforcement in the military environment, it should not only refer to normative legal rules, but what needs to be done more is to make legal breakthroughs that are more effective and efficient. The discipline of a soldier is an absolute thing that is inseparable from his duty to maintain the security of the Unitary State of the Republic of Indonesia. This study analyzes contemporary forms of threats related to security and resilience and explains the similarities and differences in national resilience studies which aim to realize a national security system and develop national security systems in other countries. This research is normative juridical research, using a statutory approach, conceptual approach, and analytical techniques in the form of grammatical interpretation and systematic interpretation. This research explains that the forms of threats that occur in Indonesia include problems at the border, intolerance between ethnicities and between governments and religions, inequality in bureaucratic reform, inadequate law enforcement, and transnational crime. This research shows that national resilience and security are influenced by the professionalism of the Indonesian National Army. The safe conditions of a country cannot be separated from just security and defense but are in synergy with other factors, namely economics, politics, law, socio-culture, ideology, geography, demography and resources